THE ELECTRONIC MARKET (MARKETPLACE) ON ELECTRONIC TRADE (E-COMMERCE) IN INDONESIA - Dyah Ochtorina Susanti (NOTARIIL Jurnal Kenotariatan, 2022)
This research is motivated by the importance of the role of the marketplace as a place for electronic commerce transaction activities between sellers and buyers that can prevent losses and provide a sense of security for both sellers and buyers. Given the importance of the role of the marketplace, it becomes a problem when questions arise regarding the legal position of the electronic market (marketplace) in electronic commerce (e-commerce) in Indonesia. Therefore, this study aims to find out the position (status or standing) electronic market law (marketplace) on trade electronics (e-commerce) in Indonesia. This study uses normative legal research with a statute legal approach and a conceptual approach. This study results of this study showed that the legal position of the marketplace in electronic commerce (e-commerce) in Indonesia includes 2 (two) things, namely the legal position as a platform and the legal position as a guarantor.